(untitled) (Economics and region, 2021)
The irrationality, disproportionality, complexity of the administrative-territorial entities of the united territorial communities are taken into consideration. It is noted, that the application of the institutional methodology of administrative and territorial development is insufficiently studied in domestic and foreign economics. Institutional inadequacy territorial division to the country’s needs has been revealed. The ways of executive power institutionalization, the development of territories in accordance with institutionalism requirements, and its role and place in administrative-territorial reform are determined. It is noted that the only institutional set of society is the institutional matrix. The institutional matrix of society is presented as a stable triad of basic elements - macro-institutions that integrate and stabilize society: economy, politics and culture. In forming a matrix, its properties are taken into account, namely the symmetry of dual positions, the interdependence of institutions within matrix, invariance of dominance, the coexistence possibility in the system of maternal matrix of different elements and matrices institutions, with native matrix obligatory dominance. The historical development of states and civilizations, existing by matrix principles above properties effectiveness has proved; otherwise the state disappears, and civilization ceases to exist. It is determined that state and regional institutional transformations generate effective reforms: administrative-territorial, economic, land and other interconnected transformations of society, including political and legal ones. Territorial development and the real economy require a governance system reform within a vertically-level management system into account natural, political, economic, ethnic, linguistic, national and other spatial and social aspects. And modernization of public administration institutions system, decentralization of powers to the level of united territorial communities should form a stable territory development system and safe economic and social environment in regions.